Emission characteristics of carbonaceous particles and trace gases from open burning of crop residues in China. (December 2015) - Ni, Haiyan; Han, Yongming; Cao, Junji; Chen, L.-W. Antony; Tian, Jie; Wang, Xiaoliang; Chow, Judith C.; Watson, John G.; Wang, Qiyuan; Wang, Ping; Li, Hua; Huang, Ru-Jin
Abstract: Open burning of crop residue is an important source of carbonaceous pollutants, and has a large impact on the regional environment and global climate change. Laboratory burn tests were conducted using a custom-made combustion chamber to determine pollutants (i.e. CO2, CO, PM2.5, organic carbon (OC) and elemental carbon (EC)) emission factors (EFs) of wheat straw, rice straw and corn stalk; the three major agricultural crop residues in China. The average EFs were estimated to be 1351 ± 147 g kg −1 for CO2, 52.0 ± 18.9 g kg −1 for CO, 10.6 ± 5.6 g kg −1 for PM2.5, 4.8 ± 3.1 g kg −1 for OC and 0.24 ± 0.12 g kg −1 for EC. In addition, the effect of fuel moisture was investigated through the controlled burning of wheat straw. Increasing the moisture content decreased the CO2 EF, and increased the EFs of CO, PM2.5 and OC. Based on measurements from this study and nationwide statistics in crop type and area, pollutants emission inventories for crop residue combustion with 1° × 1° resolution were compiled for 2008. Total emissions were 120 Tg CO2, 4.6 Tg CO, 0.88 Tg PM2.5, 0.39 Tg OC and 0.02 Tg EC. Highlights: Custom-made combustion chamber was used to determine emission factors (EFs). EFs of crop residue open burning specific to China and elsewhere were compared. Increased moisture content decreased CO2 and enhanced CO, PM2.5 & OC emissions. Emission inventories for crop residue combustion in China were compiled for 2008.